(untitled) (Research, Society and Development, 2020)
The objective of the present work was to study the effect of the addition of passion fruit albedo flour, as a proposal for full use of food, in making a cocoa brownie, as well as evaluate its technological and microbiological characteristics. For this, four brownie formulations were developed, using oatmeal (control) and its partial replacement with passion fruit albedo flour. The entire elaboration process followed the technical standards for quality control. In sequence, physical-chemical evaluations were performed (moisture, ash, total sugars, lipids, proteins, carbohydrates and color parameters) and microbiological (thermotolerant coliforms, coagulase-positive Estafilococus and Salmonella). Technological and sensory changes were noticed, so that the higher the flour content of the added passion fruit albedo, the more voluminous, dry and with a rigid consistency the brownies stayed. The results of the physical-chemical analyzes were within the parameters referenced for this type of product, maintaining characteristics favourable to the preparation of brownies. Regarding colourimetric attributes, it can be seen that the colour of the cocoa brownie has become less intense with the increase in the concentration of passion fruit albedo flour. In all microbiological aspects evaluated, the results showed compliance with the standards established by the legislation. In this way, the passion fruit albedo flour showed great potential for brownie production without interfering with its nutritional and microbiological quality.